A Synthetic Model of the Mucosa for Oral Penetration Studies - Cristina Alonso; Meritxell Martí; Anderson Ramos; Ana Cristina Calpena; Beatriz Clares-Naveros; Luisa Coderch (Membranes, 2023)
The main objective of this study is the evaluation of the use of a synthetic membrane, Nuclepore, as a model for permeation studies through sublingual mucosa. The permeability of two types of membranes, porcine sublingual oral mucosa and a synthetic Nuclepore membrane, to water was compared. Moreover, the water permeability of membranes modified with waterproofing formulations was measured to study their ability to protect against the penetration of viruses, toxins, etc. A relatively high correlation (R2 0.88) was obtained between the transmucosal water loss (TMWL) values of the artificial membrane and the mucosa. These results support the possible use of this synthetic membrane in the screening of the water permeability of formulations. In addition, studies of the permeation of different actives, drugs, and biocides through the two membranes were carried out, and these results were compared with their skin permeation data. The synthetic membrane does not seem to discern between compounds in terms of permeability. However, the permeation of caffeine through intact or modified membranes incorporating waterproofing formulations presents similar permeation profiles through the synthetic membrane and mucosa. The results from these assays should lend support to the use of this synthetic membrane when screening formulations to be applied in oral penetration studies.